Carbon fibre based flexible piezoresistive composites to empower inherent sensing capabilities for soft actuators. Issue 40 (30th August 2019) - Yan, Xue; Bowen, Chris R.; Yuan, Chenggang; Hao, Zhe; Pan, Min
Abstract : We have developed carbon fibre based flexible piezoresistive composites to fabricate a new pneumatic soft finger with an inherent sensing capability, much like a human finger. Abstract : New materials and technologies in sensing and actuation have led to the development of soft actuators and robots for biomedical systems, assistive devices, exploration and rescue. The use of integrated actuation-sensing materials in such systems is gaining interest, but there are few examples where the body of the actuator or soft robot acts as the sensing element. The development of smart soft actuators that have inherent sensing capabilities can provide advantages of high sensitivity, ease of manufacture and cost efficiency, without impairing actuator dynamics. To achieve this goal, we have prepared soft actuators using piezoresistive composites based on a silicone matrix impregnated with short conductive carbon fibres. The optimum carbon fibre volume fraction to achieve a frequency independent conductivity and piezoresistive response was determined, with in situ mechanical and electrical testing to quantify the piezoresistive properties. The frequency dependent electrical properties and sensitivity of the composites with deformation was explained on the basis of a microstructural resistor–capacitor network model. The piezoresistive composites were used to successfully manufacture a pneumatic soft finger actuator where the resistance change of the actuator body was able to monitor deformation with applied pressure. The creation of soft actuators with an inherent sensing capability is a promising approach for control and operation of future soft robots.